The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0004944114537051
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening practicum conversations: Enhancing professional learning and development through returning lecturer supervisions

Abstract: Relationships between teachers, children and university lecturers must be positive, productive and professional to optimise the learning and development of student teachers in school-based experiences. The limited research into these ‘high stakes’ relationships mostly explores alternative approaches. This paper explores the perceptions of student teachers and associate teachers as they consider the value of an alternative practicum supervision approach. The lecturers supervised and mentored the student teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, we acknowledge that other universities do require university faculty to visit preservice teachers during their field experience. The use of video-recordings could provide additional opportunities for faculty members to provide feedback to the both the pre-service and supervising teacher, particularly during aspects of classroom practice, thereby addressing issues raised in Ussher and Carss (2014). The parameters that ensure the usefulness of such feedback in the Australian context would need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we acknowledge that other universities do require university faculty to visit preservice teachers during their field experience. The use of video-recordings could provide additional opportunities for faculty members to provide feedback to the both the pre-service and supervising teacher, particularly during aspects of classroom practice, thereby addressing issues raised in Ussher and Carss (2014). The parameters that ensure the usefulness of such feedback in the Australian context would need to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In research aiming to enhance the professional conversations between university faculty and supervising teachers, Ussher and Carss (2014) point out that for pre-service student teachers "developing effective working relationships with schools and associate teachers during their practical experiences is a critical element in [their] perceptions of success" (p. 1). For Ussher and Carss, having the same university faculty visit the pre-service teacher during professional placement is beneficial for both the supervising teacher and the pre-service teacher, providing opportunities for deep reflection and further professional development.…”
Section: Professional Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…Lam (2001) examined educatorsí attitudes to classroom observation as a means of professional development and appraisal and found that participants prefer peer coaching, believing that appraisal incites pressure among teachers. Ussher and Carss (2014) studied professional learning and development through returning lecturer supervisions. They found that there should be a good relationship between the supervisor and the supervisees.…”
Section: Review Of the Literaturementioning
confidence: 99%